Impact Mechanisms of Consumer Impulse Buying in Accumulative Social Live Shopping: Considering Para-Social Relationship Moderating Role - Shugang Li; Yuqi Zhang; Yixin Tang; Wenjing Zhao; Zhaoxu Yu (Journal of Theoretical and Applied Electronic Commerce Research)
Based on para-social interaction (PSI) theory and social identity perspective, this study explores the mechanisms driving consumers’ impulse buying in social live shopping. It examines how live content design, namely information comprehensiveness (INFCOM) and interactivity (INT), affects consumer cognition and affective experiences, namely perceived usefulness (PU), PSI, and sense of belonging (SOB), to generate the influence of the urge to buy impulsively (UBI), and further explores the moderating role of the consumer–broadcaster para-social relationship (PSR) between live content design and consumer experience. Findings indicate that in an accumulative social live shopping environment, comprehensive information and strong interactivity enhance consumer social identity, reduce shopping hesitations and obstacles, and encourage UBI. Forming a close consumer–broadcaster relationship is crucial for promoting social identity and increasing UBI. Even without interactive engagement, consumers who feel a close connection with the broadcaster still experience interaction and SOB. PSR influences impulse buying by enhancing consumer perceptions and thereby promoting UBI. This study advances the understanding of impulse buying from a social identity perspective and suggests that merchants and livestream designers can improve quality and sales by providing comprehensive product information and incorporating diverse interactive elements in live broadcasts.